Integration of Ethnoscience Approach in Physics Learning Based on Laboratory Practice: A Systematic Literature Review - Ariani, Tri; Hariyadi, Bambang (Universitas PGRI Semarang, 2024)
The development of physics learning methods that integrate ethnoscience approaches and laboratory practices has become a major focus in the application of educational innovation in this modern era. This study aims to determine the development map of the number of publications examining ethnoscience-based learning; knowing which scientific articles have the highest number of citations, and knowing the development map of scientific publications based on keywords and authors. Data collection was carried out based on the Google scholar database with the keywords ethnoscience, physics learning, laboratory, practice. Data collection was carried out using Harzing's Publish or Perish (PoP) software as metadata. Data analysis was carried out using Vosviewer software as a bibliometric analysis medium. Based on the results of the article search using Harzing's Publish or Perish, 410 publications published from 2016 to 2024 were obtained for further analysis. The results showed that keyword co-occurrence analysis using VOSViewer resulted in 31 terms grouped into 4 clusters. Network and density visualization shows several keywords that often appear, namely science, education and practice. In addition, the overlay visualization illustrates the latest terms that appear in 2022 are project, critical thinking skill, physics learning, medium, physics education, and science learning. Based on the results of overlay data mapping, it can be seen that research on the topic of ethnoscience-based physics learning is still relatively new, so it is very necessary to conduct research on this topic. Meanwhile, the publication that has the highest number of citations is (W. Sumarni, S. Kadarwati) which was cited 246 times.